Prevalence and outcome of hypothyroidism in women attending antenatal clinic at J. J. M Medical College - I. S., Sapna; Mehazeena, Zainab (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Pregnancy induces physiological and metabolic changes, when overlapped with endocrine imbalance leads to undesirable consequences for both mother and fetus. Thyroid pathology has major negative impact on both mother and fetus. Hypothyroidism may be pre-existent or may begin during pregnancy; severity depends on how early and appropriately treatment is initiated. Aim of this study is to evaluate the prevalence of hypothyroidism in pregnancy and its outcome. Methods: 150 pregnant women obstetric files were studied based on their TSH value, women with TSH levels greater than 3mIU/ml who were on L-Thyroxin were included. All others who had diabetes, collagen disease, heart disease with pregnancy were excluded from the study. Results: Prevalence of hypothyroidism in pregnancy is 1.2%. Conclusions: Hypothyroidism presents with complex and serious complications with increase in maternal morbidity and perinatal mortality. To identify potential and overt hypothyroid patient thyroid screening is must during pregnancy. TSH levels should be kept less than 2mIU/L for adequate control.